(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
This article presents data on the efficiency of obtaining dry extracts from medicinal plants by subjecting the outer layers of various morphological plant organs (seeds, rhizomes, and flowers) to hydrolysis using cellulase enzyme. According to the obtained results, the application of cellulase enzyme increased the yield of extractive substances from plant raw materials by 26.8–35.8%. The results demonstrate that enzymatic treatment of different morphological organs of medicinal plants plays an important role in improving the efficiency of the extraction process.